An integrated geochemical and microbiological investigation of sulphate reduction in hypersaline pans - Porter, Donovan (Department of Geological Sciences, 2024)
Geochemical and microbiological methods were used to derive a holistic picture of sulphate reduction in five hypersaline pans in South Africa. Sulphate reduction rates were determined using a radioactive tracer (35 So/-) technique. This was applied to determination of in situ sulphate reduction rates, the effect of increased salinity on the activity of sulphate-reducers, the determination of kinetic parameters for sulphate uptake, the effect of temperature on sulphate reduction and the determination of favoured organic substrates. Such measurements were supported by the collection of pertinent geochemical data from pan sediments. The sulphate-reducing microbial community was quantified by competitive polymerase chain reaction. The structure of the microbial community was studied by denaturing gradient gel electrophoresis, from which bands were excised for DNA sequencing. Denaturing gradient gel electrophoresis patterns were analysed statistically by cluster analysis and principal components analysis. High in situ rates of sulphate reduction (up to 3684 nmol.cm-3 .daf1 ) were measured, showing strong correlations to salinity and sulphate concentrations. Rather than inhibiting sulphate reduction, slurry experiments showed increased sulphate reduction rates with increased salinity. Optimum salinities were 272-311 at hypersaline pans and 134-244 at highly saline pans. The use of compatible solutes, not K+, for osmoprotection, was inferred. Half-saturation constants measured here ( 64-780mM) are the first reported for hypersaline sites and were much higher than previously measured in other environments, implying greater regulation of sulphte transport. Values for apparent activation energy were within a narrow range (28-62 kJ.mor1 ) and similar to those measured in other environments. Sulphate reduction rates rarely increased significantly after addition of organic substrate solutions and there were no narrow substrate preferences. It was inferred that sulphate-reducers generally had sufficient organic carbon in situ. However, the use of acetate and n-butyrate suggests that complete oxidation of organic matter was more widespread than predicted on bio-energetic grounds. This was supported by DNA sequence data suggesting the presence of members of the completely-oxidising Desulfobacteraceae. Changes in bacterial numbers paralleled changes in sulphate reduction rates. Significant correlations between geochemical and microbiological data inferred from statistical analysis of denaturing gradient gel electrophoresis data revealed the importance of salinity, sulphate concentration and organic matter reactivity as determinants of SRB community structure.